2004
DOI: 10.1007/s00442-004-1652-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of behavioral and morphological plasticity on risk of predation in a Neotropical tadpole

Abstract: Predator-induced phenotypic plasticity is widespread among aquatic animals, however the relative contributions of behavioral and morphological shifts to reducing risk of predation remain uncertain. We tested the phenotypic plasticity of a Neotropical tadpole ( Rana palmipes) in response to chemical cues from predatory Belostoma water bugs, and how phenotype affects risk of predation. Behavior, morphology, and pigmentation all were plastic, resulting in a predator-induced phenotype with lower activity, deeper t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 73 publications
2
28
0
2
Order By: Relevance
“…However, the low explanatory power of the three-parameter model (r 2 =0.24; Table 3) and large standard error of the turnover estimate prevent any strong conclusions (Table 2). We have previously observed variable growth rates in tadpoles of this species even within a single experimental pool (McIntyre et al 2004), and such differences probably contributed to inconsistent 15 N enrichment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the low explanatory power of the three-parameter model (r 2 =0.24; Table 3) and large standard error of the turnover estimate prevent any strong conclusions (Table 2). We have previously observed variable growth rates in tadpoles of this species even within a single experimental pool (McIntyre et al 2004), and such differences probably contributed to inconsistent 15 N enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…2). Tadpole growth rates in field enclosures and experimental pools at our study site average 0.6-1.4% per day (McIntyre et al 2004;Solomon et al 2004), potentially accounting for all of the N turnover observed in this study. Though no data are available for the snail species, our observations under experimental and field conditions suggest that their growth rates are much lower than the observed turnover rates of muscle N (see also Kemp et al 1990).…”
Section: Factors Affecting N Turnover Ratesmentioning
confidence: 98%
“…Amphibian larvae are partially protected from predation by a suite of traits that includes a deep tail fin and tail muscle (McCollum and Van Buskirk 1996, Van Buskirk and McCollum 2000a, Van Buskirk and Schmidt 2000, McIntyre et al 2004, Teplitsky et al 2005). The functional consequences of variation in tail shape are not fully understood.…”
Section: Relationships Between Morphology and Habitat Gradientsmentioning
confidence: 99%
“…Beispiele für umweltinduzierte morphologische Plastizität sind z. B. durch Prädatoren ausgelöste Veränderungen von Körperformen bei Beutespezies (McIntyre et al 2004), durch physisches Training ausgelöste Veränderungen der Muskelstruktur (Johnston 2006), oder durch Temperaturund Nahrungsschwankungen induzierte morphologische Veränderungen in zentralen Stoffwechselorganen wie der Leber bei Wirbeltieren oder der Mitteldarmdrüse bei Wirbellosen (Braunbeck et al 1987;Segner und Möller 1984;Vogt et al 1986;Dittbrenner et al 2008). Entsprechend führt auch die Belastung mit toxischen Stoffen zu morphologischen Veränderungen in Zielorganen und -zellen (Au 2004;Braunbeck et al 1989;Braunbeck 1998;Burkhardt-Holm et al 1998;Gernhöfer et al 2001;Hinton et al 1978Hinton et al , 2008Köhler et al 1992;Triebskorn und Künast 1990;Vogt 1987).…”
Section: Problemstellungunclassified